Effective suppression of atrial fibrillation by ivabradine: Novel target for an established drug?. (1st June 2017) - Frommeyer, Gerrit; Sterneberg, Magdalena; Dechering, Dirk G.; Ellermann, Christian; Bögeholz, Nils; Kochhäuser, Simon; Pott, Christian; Fehr, Michael; Eckardt, Lars
Abstract: Background: Ivabradine is an inhibitor of mixed Na + -K + -currents and routinely administered in chronic heart failure. Clinical studies reported divergent trends regarding proarrhythmic and antiarrhythmic effects in atrial fibrillation (AF). Methods and results: In 12 isolated rabbit hearts AF was induced in 7 of 12 hearts (13 episodes) under baseline conditions by a standardized protocol employing atrial burst pacing. Thereafter, a combination of acetylcholine and isoproterenol was employed to enhance AF occurrence. Monophasic action potential recordings showed a decrease of atrial action potential duration (aAPD, -37 ms, p  < 0.05) and atrial effective refractory period (aERP;-39 ms, p  < 0.05) after infusion of both acetycholine (1 μM) and isoproterenol (1 μM) as compared with baseline. This led to induction of AF in 11 of 12 hearts (124 episodes). Simultaneous infusion of ivabradine (3 μM) led to a significant reduction of AF (6 of 11 hearts, 63 episodes). Ivabradine induced an increase of aAPD (+ 9 ms) and aERP (+ 30 ms, p  < 0.05) leading to a marked increase of atrial post-repolarization refractoriness (aPRR), defined as the difference of aERP and aAPD (+ 21 ms, p  < 0.05). Results were compared to 10 rabbits treated with flecainide. Flecainide treatment also induced a significant increase of aPRR and resulted in induction of AF in 6 of 10 hearts (58 episodes) while 9 of 10 hearts were inducible during sole treatment with acetylcholine and isoproterenol (129 episodes). Conclusion: In the present experimental study, administration of ivabradine reduced inducibility of AF and therefore may represent a supplemental therapeutic option in AF. Of note, its antiarrhythmic efficacy was comparable to the established agent flecainide.